In Celebration of the K8 Telephone Kiosk – Britain's Last Red, Cast-Iron Phonebox. (2nd July 2020) - Linge, Nigel; Sutton, Andy; Hurley, Andrew; Johannessen, Neil
ABSTRACT: Whilst every country in the world has introduced phoneboxes onto its streets, the United Kingdom stands alone in having adopted the red phonebox as a symbol of its national identity. However, that symbol is of phonebox designs produced by Giles Gilbert Scott in 1925/35 and not of the more contemporary ones that followed it. When introduced in 1968, the Bruce Martin-designed K8 kiosk or phonebox was hailed as a masterpiece of industrial design, yet today it has virtually disappeared. It was the last of the British red, cast-iron phoneboxes and despite over 11, 000 being manufactured, less than one percent survive. Telecommunications is a rapidly changing field that brings enormous challenges for the heritage movement, as the K8 story illustrates, requiring a far more agile approach in respect of contemporary collecting policies and improved procedures for protection and preservation. This paper traces the evolution of the British phonebox, focusing on the circumstances that led to the development of the K8 and describes in detail its design. A gazetteer of those K8s that are known to survive is also included.